Peran Street-level Bureaucrats dalam Implementasi Program Keluarga Harapan (PKH) di Desa Caturharjo, Kecamatan Sleman, Kabupaten Sleman (STUDI KASUS: Desa Caturharjo, Kecamatan Sleman, Kabupaten Sleman) - , Mega Hendra Waty ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Program Keluarga Harapan (PKH) is a government program in order to deal with poverty that provides social security in form of conditional cash transfer for very poor household. The objective of PKH is to decrease poverty through providing access to education and health service. Implementation of PKH has been done since 2007 in several cities in Indonesia that involves street-level bureaucratsâs role. But implementation of PKH is still far from expectation because there are still corruptions done by advisor of PKH itself. Different from other cities, Caturharjo Village applied a successful PKHâs fund distribution toward target group. Based on that fact, this research is aimed to analyze roles of street-level bureaucrats in implementation of PKH and performance of implementation PKH through several indicators in research field. Theories that are used in this research are theory of public policy, theory of policy implementation, theory of street-level bureaucrats and the role of street-level bureaucrats. This research was done in PKH of Caturharjo village. Meanwhile, method of this research is descriptive qualitative. Collecting dataâs method was using primary data, with in-depth interview, direct observation, and analysis secondary data source. This research shows that implementation of PKH in Caturharjo Village is done successfully. That result is based on the analysis of indicators of policy performance, those are bias, service delivery, frequency, coverage, access, and accountability, which are done with good results. Street-level bureaucrat is the most determined factors among others that helps implementation of PKH run successfully. There are some important roles of street-level bureaucrats which are providing information about PKH, doing clarification and updating data, doing socialization and training PKHâs staff in the district level, managing complains, maintaining communications within different stakeholders who are involved in PKH, doing control mechanism, and verifying commitment of target group in education and health aspects. There are some recommendations to improve performance of implementation of PKH. (1) It can be a feedback for government if they intend to formulate and implement another policy that has similarity with PKH in which government can make a scheme for street-level bureaucrats to be one of the important stakeholders that help policy implementation successful (2) Ministry of Social Affairs has to make mechanism control in order to monitor the fund-flow that is used by the target group (3) Adding PKH advisor especially for the district which has a lot of very poor household like Caturharjo Village (4) Making contract about cooperation agreement among Department of Health, Department of Education, and Department of Social to make sure they are willing to help the implementation of PKH.